Four Lymphomas in 1 Patient: A Unique Case of Triple Composite Non-Hodgkin Lymphoma Followed by Classical Hodgkin Lymphoma. (May 2017) - Tennese, Alysa; Skrabek, Pamela J.; Nasr, Michel R.; Sekiguchi, Debora R.; Morales, Carmen; Brown, Theresa C.; Weisenburger, Dennis D.; Perry, Anamarija M.
Composite lymphomas consist of 2 or more distinct lymphomas occurring in a single anatomical site or simultaneously in different sites and can be composed of any combination of B-cell non-Hodgkin lymphoma (NHL), T-cell NHL, or Hodgkin lymphoma (HL). Cases of composite lymphomas with more than 2 lymphomas are extremely rare, with only 4 reports in the literature. We report the case of a 49-year-old man with a triple composite lymphoma in a single lymph node, consisting of small lymphocytic lymphoma, follicular lymphoma, and mantle cell lymphoma in situ. The patient received multiple courses of chemotherapy and an autologous stem cell transplant, which resulted in complete remission. Then, 6 years after the stem cell transplant, he developed classical HL. This unique case is, to our knowledge, the first report of a patient with triple composite lymphoma consisting of 3 small mature B-cell NHLs, who subsequently developed a fourth lymphoma.